Martin Luther King, Jr. - Colaiaco, James A. author. aut Link
X, 238 p.
Keywords: In this exemplary work of scholarly synthesis the author traces the course of events from the emergence of Martin Luther King, Jr. as a national black spokesman during the Montgomery bus boycott to his radical critique of American society and foreign policy during the last years of his life. He also provides the first in-depth analysis of King's famous Letter from Birmingham Jail - a manifesto of the American civil rights movement and an eloquent defence of non-violent protest.